(untitled) (Confluenţe Bibliologice, 2021)
This article inserts the history of treasures or the multitude of tumul, mounds of antiquity and prehistory, legacies of the Scythians, Geth, Greeks, mounds scattered everywhere: tumul from Constanța, around Mangalia. In Bessarabia there are tumul in the Balti area; Saharna Nuoa, Tiglau; on a high plateau on the right bank of the Dniester River; near Iezarenii Vechi, Sangerei district. The author highlights their presence and location, the forms, the territorial arrangement that is still preserved, the opinions of the specialists.